2021
DOI: 10.2147/ott.s305248
|View full text |Cite
|
Sign up to set email alerts
|

Targeted-Gene Sequencing and Bioinformatics Analysis of Patients with Pancreatic Mucoepidermoid Carcinoma: A Case Report and Literature Review

Abstract: Background Primary pancreatic mucoepidermoid carcinoma (MEC) is an extremely rare malignant tumor with unclear etiology and pathogenesis. There are only eleven reported cases in English papers published from 1959 to 2020. MEC generally occurs in the salivary gland, but cases in the pancreas have also been reported. Although being considered as a low-grade indolent carcinoma, pancreatic MEC always invades the surrounding lymph node and metastasizes. The prognosis of pancreatic MEC is unsatisfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, it is exceedingly rare in the pancreas. Since Franz first reported pancreatic MEC in 1959, only 13 cases have been reported in English literature [ 3 ] ( Table 1 ). Pancreatic MEC is more commonly found in the body and tail of the pancreas, and the liver and lymph nodes are the sites where metastasis is more likely to occur [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is exceedingly rare in the pancreas. Since Franz first reported pancreatic MEC in 1959, only 13 cases have been reported in English literature [ 3 ] ( Table 1 ). Pancreatic MEC is more commonly found in the body and tail of the pancreas, and the liver and lymph nodes are the sites where metastasis is more likely to occur [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mucoepidermoid Carcinoma (MEC) is a common primary malignant tumor of the salivary glands [ 1 ], first described by Stewart et al in 1945 [ 2 ]. Pancreatic mucinous epidermoid carcinoma is even rarer, to our knowledge, with only 13 cases reported in English literature [ 3 ]. Diagnosis of MEC still relies on pathological examination due to the absence of typical imaging characteristics and tumor markers.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review suggests that many gene mutations are implicated in the pathogenesis of neoplasms. 66 Li et al 24 found that the FAT1 gene is mutated in HAL tissues, with the mutation forms at c.3940T (Thymine)>A (Adenine). Because of the similarities of the tissue characteristics and pathologies of HLA, HCC, and lung adenocarcinoma (LUAD), the potential biological mechanisms of liver hepatocellular carcinoma (LIHC) and LUAD were discussed and compared together in this study.…”
Section: Discussionmentioning
confidence: 99%